Hodnocení finanční situace podniku a návrhy na její zlepšení - Šťastný, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce je zaměřena na hodnocení finanční situace firmy PREFA BRNO a.s. v letech 2005 až 2014. Hodnocení je prováděno metodami finanční analýzy, zdrojem informací jsou účetní výkazy analyzované firmy. Na základě výsledků finanční analýzy navrhuje práce řešení problémových oblastí.

The bachelor’s thesis is focused on evaluation of the financial situation of the company PREFA BRNO a.s. from 2005 to 2014. Evaluation is carried out by methods of financial analysis, sources of information are the financial statements of the analyzed company. Based on the results of the financial analysis it proposes solving of the problem areas.
Evaluation of the Financial Situation of the Company and Proposals for its Improvement
Keywords: Finanční analýza; hodnocení finanční situace podniku; rozvaha; výkaz zisku a ztráty; finanční situace; Financial analysis; Evaluation of the Financial Situation of a Company; balance sheet; profit and loss statement; financial situation